1998
DOI: 10.1046/j.1365-2133.1998.02471.x
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of standardized skin surface biopsy in measurement of the density of Demodex folliculorum. A case report

Abstract: Standardized skin surface biopsy (SSSB) is an appropriate method for measuring the density of Demodex folliculorum (Dd). Nevertheless, the observation of a clinical case demonstrates that, contrary to what was presumed before, a single SSSB can fail to collect the complete biotope of the mite. This could give rise to false negative results regarding the measurement of Dd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
77
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(82 citation statements)
references
References 12 publications
3
77
0
2
Order By: Relevance
“…They are mainly found in the pilosebaceous glands and their density is normally less than 5 mites/cm 2 of skin (Sakuntabhai andTimpatanapong 1991, Forton andSong 1998). Factors controlling the presence and density of D. folliculorum are poorly known (Aydingoz et al 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are mainly found in the pilosebaceous glands and their density is normally less than 5 mites/cm 2 of skin (Sakuntabhai andTimpatanapong 1991, Forton andSong 1998). Factors controlling the presence and density of D. folliculorum are poorly known (Aydingoz et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Demodicidosis occurs throughout the world, and the incidence of infestation is related to age (Sakuntabhai andTimpatanapong 1991, Forton andSong 1998). Recent reports of demodicidosis in association with acquired immunodeficiency syndrome (AIDS) and cancer chemotherapy have suggested that immune deficiency may be associated with the multiplication of this mite (Castanet et al 1997, Patrizi et al 1997, Aydingoz et al 2000, Jansen et al 2001, Damian and Rogers 2003.…”
Section: Discussionmentioning
confidence: 99%
“…Using adhesive tapes, comedo extraction, hair epilation, skin impression/scraping, skin biopsy, and skin surface biopsy are the most commonly used techniques in this regard (13,14,34). We chose the SSSB technique owing to its non-invasiveness and high sensitivity compared with the other available methods (12,35).…”
Section: Discussionmentioning
confidence: 99%
“…Demodex spp. proliferasyonu püstüler follikülit, pitriazis follikülorum, papülopüstüler ve granülomatöz rozasea gibi dermatolojik sorunlara neden olabilmektedir (10,11) . Polat ve ark.…”
Section: Discussionunclassified